A Gauss–Newton inversion method based on prior back‐projection information for inverse scattering problems. Issue 4 (4th January 2022) - Chen, Wei; Du, Liuge; Zhao, Jia; HuYan, Siteng
Abstract: Gauss–Newton inversion (GNI) method uses a microwave imaging system to reconstruct the dielectric properties of the target area with high accuracy. But the computational complexity of this method increases significantly as the target area and imaging resolution increase. At present, computed tomography (CT) and magnetic resonance imaging (MRI) are used in some researches to provide prior information for GNI algorithm to decrease computational complexity. However, these methods cannot be achieved by microwave imaging system. In this letter, a fast and high‐precision imaging approach combining back‐projection (BP) algorithm with GNI algorithm by using the same set of microwaves equipment is proposed. The size of reconstructed area is reduced and a more suitable initial value is predetermined according to the prior information provided by BP fast imaging algorithm. The permittivity distribution of the target area is then reconstructed by GNI algorithm. Numerical simulations are presented to verify that the use of BP prior information improves the real‐time performance and accuracy of the whole algorithm.